Experimental Study on the Hydrodynamic Resistance of a 265 GT Fishing Vessel with Wind-Assisted Propulsion - Fatihah, Anandita; Rina, Rina; Sari, Dian Purnama; Utina, Muhammad Ridwan; Sulistyawati, Wiwin (Department of Naval Architecture - Diponegoro University, 2026)
This study experimentally evaluates wind-assisted propulsion (WASP) to reduce the resistance of a 265 GT fishing vessel using model-scale towing tank test conducted at the PRTH-BRIN towing tank facility, with towing forces measured using calibrated resistance dynamometers following ITTC recommended procedures. Bare-hull resistance was measured at seven speeds over Froude numbers Fr 0.12 – 0.30, while tests with the wing sail installed were conducted at three speeds in the upper range (Fr 0.18 – 0.30) under steady beam wind conditions corresponding to a full-scale true wind speed of 20 knots. Towing-force measurements were converted into total resistance and total resistance coefficients. The wing sail effect was quantified using the wind-assisted percentage (WA%), defined as the relative reduction in resistance compared with the bare-hull condition at the same speed. A Type B uncertainty analysis following ITTC Recommendations was performed for the bare-hull measurements. The results show that, for the tested wind-assisted condition, the wing sail configuration produced lower resistance than the bare-hull at the same speed. The absolute resistance reduction increases with Froude number, reaching about 1.06 N at the highest speed, whereas WA% decreased from about 4.53% to 2.25% indicating a larger relative benefit at lower end of the tested speed range. The expanded relative uncertainty of bare-hull resistance is below 4% for all operating points. Overall, the experiments indicate a measurable wind-assisted contribution from the wing sail and provide a practical framework for assessing WASP performance at model scale using WA% as an indicator.